REKRUTMEN ELIT BIROKRASI DI LINGKUNGAN SEKRETARIAT DAERAH PROVINSI JAWA TENGAH TAHUN 2013-2015 - Rr. Farasita Anggit Purnandini; Warsito Warsito; Budi Setiyono (Journal of Politic and Government Studies, 2015)
In implementation of Government in Indonesian, region given a chance and freedom for organize the extensive of region autonomy, which it is included in section 18 and verse 5 of UUD 1945. From awarding the authority, the low level of bureaucrat given a chance for take the initiative and explore them creativity. Therefore the main problem of realization autonomy region is upgrading the quality of human power and agency. We need human power which qualified and professional. Qualified and professional human power depends on process of recruitment bureaucracy elite. Therefore the formulation of problem in this research is “How is the process of recruitment bureaucracy elite in area of Central Java Provincial Secretariat and what is the factor affecting.”            The direction of this research is to detect how is process of recruitment bureaucracy elite in area of Central Java Pronvicial Secretariat and what is the factor affecting of process recruitment. The research method is descriptive qualitative. Primary source data retrieved from interview and secondary data from document, archieve, and the other source which it is still connect with research. Analysis technique using qualitative data with analyst in form essay, depiction, and drawing the conclusion of indication research.            From the result of research, showing that process of recruitment bureaucracy elite in area of Central Java Pronvicial Secretariat using auction of position system or open promotion system. It was first time perfomed in Central Java. The result of this system judged can fixing the situation of our bureaucracy because a few of good governance idea which it is include idea of transpiration, accountability, obey the law, and participation of the citizen. Besides the advantage of open promotion system is recruitment system that puts meritocracy people on front.            This recruitment system have to done truly and full of concistency, so that the result not useless. Also required commitment, courage, and provide a leadership in Indonesian, in particular the leadership of leaders such as, Governor, Regent, or Mayor in order to apply the punishment for all of the agency which make a mistake in the process recruitment.Keywords: recruitmen, Elite, Bureaucracy